Immunomodulatory properties of naïve and inflammation-informed dental pulp stem cell derived extracellular vesicles - Umar, Sadiq; Debnath, Koushik; Leung, Kasey; Huang, Chun-Chieh; Lu, Yu; Gajendrareddy, Praveen; Ravindran, Sriram (Frontiers in Immunology, 2024)
Mesenchymal stem cell derived extracellular vesicles (MSC EVs) are paracrine modulators of macrophage function. Scientific research has primarily focused on the immunomodulatory and regenerative properties MSC EVs derived from bone marrow. The dental pulp is also a source for MSCs, and their anatomical location and evolutionary function has primed them to be potent immunomodulators. In this study, we demonstrate that extracellular vesicles derived from dental pulp stem cells (DPSC EVs) have pronounced immunomodulatory effect on primary macrophages by regulating the NFκb pathway. Notably, the anti-inflammatory activity of DPSC-EVs is enhanced following exposure to an inflammatory stimulus (LPS). These inhibitory effects were also observed in vivo. Sequencing of the naïve and LPS preconditioned DPSC-EVs and comparison with our published results from marrow MSC EVs revealed that Naïve and LPS preconditioned DPSC-EVs are enriched with anti-inflammatory miRNAs, particularly miR-320a-3p, which appears to be unique to DPSC-EVs and regulates the NFκb pathway. Overall, our findings highlight the immunomodulatory properties of DPSC-EVs and provide vital clues that can stimulate future research into miRNA-based EV engineering as well as therapeutic approaches to inflammation control and disease treatment.